2011
DOI: 10.4061/2011/918017
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hepatitis B in Decompensated Liver Cirrhosis

Abstract: Chronic hepatitis B infection progresses from an asymptomatic persistently infected state to chronic hepatitis, cirrhosis, decompensated liver disease, and/or hepatocellular carcinoma. About 3% of patients with chronic hepatitis develop cirrhosis yearly, and about 5% of individuals with hepatitis B cirrhosis become decompensated annually. The outcome for patients with decompensated cirrhosis is bleak. Lamivudine, the first oral antiviral agent available for hepatitis B treatment is safe and effective and can i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 78 publications
0
30
0
3
Order By: Relevance
“…In patients with decompensated cirrhosis who are ineligible for liver transplantation, optimal medication management is important to reduce and manage decompensation events and reduce or delay unplanned hospital admissions. Pharmacotherapy for specific disease etiologies, such as chronic hepatitis B or C, may also lead to improvement in liver function and survival . However, medication‐related problems (MRPs), such as nonadherence, mismanagement related to poor patient understanding, and suboptimal monitoring, have been linked with early hospital readmission and substantial resource burden in this group .…”
Section: Mrp Categories and Subtypes Adapted From Hepler And Strandmentioning
confidence: 99%
“…In patients with decompensated cirrhosis who are ineligible for liver transplantation, optimal medication management is important to reduce and manage decompensation events and reduce or delay unplanned hospital admissions. Pharmacotherapy for specific disease etiologies, such as chronic hepatitis B or C, may also lead to improvement in liver function and survival . However, medication‐related problems (MRPs), such as nonadherence, mismanagement related to poor patient understanding, and suboptimal monitoring, have been linked with early hospital readmission and substantial resource burden in this group .…”
Section: Mrp Categories and Subtypes Adapted From Hepler And Strandmentioning
confidence: 99%
“…Hepatit B virusu (HBV)'na bağlı kompanse sirozlu hastalarda sepsis ve dekompansasyon riski nedeniyle interferon (IFN) tedavisi yeğlenmez; verilecekse de yakın izlem altında verilmelidir (1). Oral antiviraller olarak ilk seçenekler yüksek potensli ilaçlar olan entekavir (ETV) ve tenofovir (TDF)'dir.…”
Section: Kompanse Ve Dekompanse Sirozlu Hastalarda Kronik Hepatit B Tunclassified
“…Dekompanse sirozu olan KHB hastalarında ölümlerin çoğunun tedavinin ilk 6 ayında meydana geldiği ve tedavi öncesindeki bilirübin, kreatinin ve HBV DNA düzeylerinin artmış olmasının yüksek risk faktörleri olduğu saptanmış-tır. HBV replikasyonunun erken baskılanmasıyla olumlu sonuçlar alınması mümkündür (5 aşamada uygulanır: [1] Karaciğer nakli süresince, anhepatik fazda, intravenöz (İV) olarak 4000-10000 İÜ; [2] nakil sonrası 3-7 gün süresince, intramüsküler (İM) veya İV 2000-10000 İÜ/gün; [3] nakli izleyerek anti-HBs düzeyi 100 İÜ/lt üzerinde tutulacak şekilde yüksek doz (10000 İÜ/ay) ya da düşük doz (400-2000 İÜ/14 gün veya 3000-6000 İÜ/ay veya 10000 İÜ/2-3 ay) verilir (6,8). İdame dozu ya seçilen sabit bir miktarda uygulanır ya da çoğu merkezde yeğlendiği gibi alıcının anti-HBs düzeyi izlenerek belirlenir.…”
Section: Kompanse Ve Dekompanse Sirozlu Hastalarda Kronik Hepatit B Tunclassified
“…Decompensated HBV patients receiving oral NAs must be monitored frequently (every 3 months) for virological and clinical response, the patients’ compliance, drug resistance and adverse effects . Renal function and lactic acidosis should be monitored in these patients, especially in those with a model for end‐stage liver disease (MELD) score > 20 .…”
Section: Monitoringmentioning
confidence: 99%
“…2,7 MONITORING Decompensated HBV patients receiving oral NAs must be monitored frequently (every 3 months) for virological and clinical response, the patients' compliance, drug resistance and adverse effects. 10 Renal function and lactic acidosis should be monitored in these patients, especially in those with a model for end-stage liver disease (MELD) score > 20. 2 One systematic review 11 has shown that among patients receiving antiviral therapy, cirrhosis, HBeAg-negative at baseline and failure to remain in virological remission were associated with an increased risk of HCC.…”
Section: Selection Of Antiviral Therapymentioning
confidence: 99%